THE CONTRIBUTION OF ARM LENGTH, ARM EXPLOSIVE POWER, BACK TRUNK FLEXIBILITY, FOOTBALL.THROW-IN ABILITY OF TAMANGAPA ELEMENTARY SCHOOL STUDENTS - M. Imran Hasanuddin (STKIP Paris Barantai, 2025)
This research is a type of quantitative descriptive research that uses a